[OP.LB.02.03] EFFECTS OF MULTIELECTRODE RENAL DENERVATION ON SYMPATHETIC NERVE ACTIVITY AND INSULIN RESISTANCE IN METABOLIC SYNDROME. (September 2016) - Tsioufis, C.; Dimitriadis, K.; Kasiakogias, A.; Kalos, T.; Liatakis, I.; Koutra, E.; Nikolopoulou, L.; Lau, E.; Papademetriou, V.; Tousoulis, D.
Abstract : Objective: This study aimed to investigate the effects of renal denervation (RDN) on sympathetic nerve activity and insulin resistance in patients with metabolic syndrome at 3 months post-RDN. Design and method: Seventeen patients fulfilled 4/5 criteria for metabolic syndrome and under stable use of at least two anti-hypertensive drugs at maximum tolerated doses for at least 4 weeks were enrolled and randomized in 3:1 ratio to RDN [n = 13, 12 males, age: 58 ± 7 years] and Control groups [n = 4, 3 males, age: 60 ± 5 years]. Both groups were followed up for 3 months. Muscle sympathetic nerve activity (MSNA) measurements were performed to assess sympathetic nerve activity at fasting state and during standard 75 g oral glucose tolerance test (OGTT). Blood sampling was also performed to assess insulin resistance (HOMA-IR). Results: In the RDN group, office BP reduced by 16 ± 21/10 ± 11 mmHg (P = 0.01/0.007); average 24-hour BP reduced by 14 ± 16/5 ± 8 mmHg (P = 0.008/0.03); waist circumference reduced by 3.1 ± 3.6 cm (P = 0.008); and MSNA at fasting state reduced from 55 ± 10 bursts per minute/82 ± 15 bursts per 100 heart beats to 46 ± 8 bursts per minute/71 ± 15 bursts per 100 heart beats (P = 0.0008/0.006) at 3 months post-RDN. During OGTT, while blunted MSNA responses were noted at baseline throughout the 120-minute test (P > 0.05/0.05 vs. MSNA at fasting state), improved MSNA responses with burst frequency/burst incidence increased to 52 ± 8 bursts per minute/76 ± 12 bursts per 100 heart beats (P < 0.001/0.04 vs. the MSNA at fasting state, n = 13) at 30 minutes and to 58 ± 16 bursts per minute/80 ± 14 bursts per 100 heart beats (P = 0.04/0.008 vs. the MSNA at fasting state, n = 10) at 120 minutes were observed at 3 months post- RDN. No such improvements were observed in the 4 control group subjects at 3 months follow-up. No statistical significant change was observed in the HOMA-IR in both groups at 3 months. Conclusions: Strategies to target specifically the elevated sympathetic nerve activity may provide substantial clinical benefits to patients with metabolic syndrome and associated hypertension.